Edukasi Tentang Asi Dan Manajemen Laktasi Kota Makassar - Imelda Iskandar; Sumarni Sumarni; Julia Novita (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2020)
The nutritional problems faced in Indonesia today remain the same, namely that many children suffer from malnutrition. The national movement to increase breastfeeding is one of the government's efforts to improve the health status of mothers and children. However, the achievement of exclusive breastfeeding has not been achieved, one of the reasons is the breastfeeding factor. Meanwhile, the point in the success of providing exclusive breastfeeding and continuing it for up to 2 years is related to a mother's understanding of lactation management. So this service activity is carried out to teach mothers who are young pregnant, late pregnant and have just given birth to a 1 month old baby to participate so that their knowledge increases. The method in this activity is a pre-test before providing information related to breastfeeding and lactation management, then continuing with the post-test to see the success of the activity. The mothers' enthusiasm was seen to be very high and resulted in a strong determination to be able to provide exclusive breast milk to their babies. The success rate of this activity was 80%, judged from the responses and questions from the participants.